2019
DOI: 10.22159/ijpps.2019v11i3.25930
|View full text |Cite
|
Sign up to set email alerts
|

Food–drug Interaction and Their Clinical Implications: Selected Investigations

Abstract: Food-drug interactions occur as a result of pharmacokinetic or pharmacodynamics mechanisms. Pharmacokinetic mechanisms include what the body does to a drug while Pharmacodynamics mechanisms involve what drugs do to the body. Many types of food have been shown to influence metabolism and the absorption of drugs. Large numbers of drugs are produced and introduced yearly. The interaction between Food and drug may cause negative effects in the nutritional status of the patient as well as safety and efficacy of dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…In the acute test, the study showed an elevated white blood cell count in rats administered papaya extract, compared to Ruzu bitters and control rats (Figure 3). This is in line with previous studies which stated that papaya leaves extract exhibits antitumor activity via its immunomodulatory properties [34,35]; another study equally supported its health-promoting and immunoprotective effects [36].…”
Section: Discussionsupporting
confidence: 91%
“…In the acute test, the study showed an elevated white blood cell count in rats administered papaya extract, compared to Ruzu bitters and control rats (Figure 3). This is in line with previous studies which stated that papaya leaves extract exhibits antitumor activity via its immunomodulatory properties [34,35]; another study equally supported its health-promoting and immunoprotective effects [36].…”
Section: Discussionsupporting
confidence: 91%
“…The papaya plant "Carica papaya" is a perennial medicinal plant that is easy to grow and adapts to various soils (Agboola et al, 2018). Many studies have shown that the plant exhibits various antimicrobial properties (Abd Elgadir et al, 2014) including anthelmintic (Soedji et al, 2017), anticoccidial (Hema et al, 2015;Dakpogan et al, 2018) and immune system enhancing (Muazu and Aliyu-Paiko, 2020). Most studies on the use of Carica papaya seeds in poultry farming have focused mainly on their anthelmintic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Papaya is sweet, flavorful, brightly colored, and uniquely rich in vitamin C and carotenoids, making it rank first on nutritional scores among 38 common fruits and also rank first among fruits consumed [3,4]. Papaya also has valuable medical and industrial applications, including the production of a well-known proteolytic enzyme, papain [5][6][7][8][9]. Water balance is particularly important for this special species because a large amount of water is essential for the crop yield and quality [10,11].…”
Section: Introductionmentioning
confidence: 99%